Réponses

Meilleure réponse !
2014-01-14T00:27:52+01:00
Bonsoir

(a² + b²)(c² + d²) = a²c² + a²d² + b²c² + b²d²

(ac + bd)²+ (ad - bc)² = (a²c² + 2acbd + b²d²) + (a²d² - 2adbc + b²c²)
                                     = a²c² + 2abcd + b²d² + a²d² - 2abcd + b²c².
                                     = a²c² + b²d² + a²d² + b²c²
                                     = a²c² + a²d² + b²c² + b²d²

Les membres de droite étant égaux, on en déduit que les membres de gauche le sont également.

Par conséquent,  (a² + b²)(c² + d²) = (ac + bd)²+ (ad - bc)²